Epigenética na reprogramação celular e no desenvolvimento embrionário - Glanzner, Werner Giehl (2016)
Epigenetic programming is the main mechanism regulating cell function and gene expression, through the activation or repression of transcriptional activity. In addition, epigenetics is closely related to reproductive events such as cell reprogramming and embryo development. In the first study, the effects of the germinal vesicle (GV) oocyte extract alone, or in combination with the deacetylase inhibitor Scriptaid, on porcine somatic cell reprogramming were evaluated. The formation of stem cell-like colonies were observed approximately two weeks after treatment with oocyte extract or oocyte extract plus Scriptaid. The colony number, at the time of appearance and after 48 hours, was similar between treatments. Partial activation of pluripotent, chromatin modifying and DNA methylating genes such as Ezh2 and Dnmt1, was observed three days after the oocyte extract treatment. However, the mRNA expression levels of the previous genes were similar to the control 15 days after treatment. This data suggest that GV oocyte extract is able to induce limited reprogramming in porcine fibroblasts, seen here by the partial activation of these genes. In the second study, brahmarelated gene-1 (BRG1), a cofactor and activator of chromatin modifications, and lysine demethylase 1A (Kdm1A), a repressor of gene expression, were characterized during porcine embryo development. Kdm1A is involved in the demethylation of both mono- and dimethylations, H3K4me and H3K4me2, respectively, on lysine 4 of histone 3. Firstly, we observed that proteins for both factors (BRG1 and Kdm1A) were absent in the nuclei of metaphase II oocytes, however, the proportion of nuclear localization increased on day 3-4 of embryo development. This time point coincides with the embryonic genome activation (EGA) in swine. Furthermore, using a well-established model of embryo developmental competence, based on time of first cleavage, it was verified that these factors were regulated during embryo development and are correlated with mRNA expression of other demethylases and H3K4me and H3K4me2 levels during EGA. It was also observed that BRG1 and Kdm1A levels are correlated with embryo cell numbers during EGA. These data suggest that BRG1 and Kdm1A participate in the regulation of H3K4 methylation during embryonic genome activation, and consequently, embryo development in swine.